Coagulation Abnormalities and Management in Hospitalized Pediatric Patients With COVID-19. Issue 7 (7th June 2022) - Noni, Maria; Koukou, Dimitra-Maria; Tritzali, Maroula; Kanaka-Gantenbein, Christina; Michos, Athanasios; Spoulou, Vana
Abstract : Background: The incidence and severity of coagulation abnormalities have not been extensively studied in pediatric populations with coronavirus disease 2019 (COVID-19). Moreover, their association with an increased risk for thromboembolic events remains unclear, and there is a lack of evidence for optimal prophylactic antithrombotic management. The aim of our study was to present our experience in evaluation, management, and long-term outcomes of coagulation abnormalities in pediatric hospitalized patients with COVID-19. Methods: A prospective study was performed in all children hospitalized for COVID-19 during a 6-month period focusing on patients' coagulation abnormalities, the normalization of the coagulation profile with or without anticoagulation prophylaxis and the clinical outcome of the disease. Results: Two hundred twenty-three patients (median age: 11.4 months) were enrolled in the study. Coagulation abnormalities were detected in 92.4% of patients with increased D-dimer levels to be the most common abnormality detected in 84.3% of patients. Prophylactic anticoagulation was initiated only in 7 (3.1%) selected patients with severe COVID-19 and at least 2 risk factors for venous thromboembolism (VTE) and in all patients with previous history of VTE. Follow-up coagulation profile in 85 patients showed that changes over time had a tendency towards normalization irrespectively of the initiation of anticoagulant thromboprophylaxis. No thrombotic complications were observed 3 months upon discharge. Conclusions: Although abnormal findings in coagulation profile were very common, they were not associated with risk for VTE even in severe cases. A trend of normalization early in the course of the disease was observed regardless of the use of anticoagulant thromboprophylaxis.